Case-area targeted interventions (CATI) among household contacts and neighboring households after identifying cholera hotspot: a study protocol for the effectiveness of Oral Cholera Vaccine (OCV) and its potential impact on cholera control - Imam Tauheed; Afroza Akter; Md. Taufiqur Rahman Bhuiyan; Md. Shahinur Rahaman; Al Amin Ahmed Shakil; Sadia Sabrina; Istiaque Hossain; Hassan Afrad; Prasanta Kumar Biswas; Md. Amiruli Islam Bhuiyan; Sadia Isfat Ara Rahman; Marjahan Akhtar; et al. (BMC Public Health, 2026)
Abstract Background Cholera outbreaks and epidemics are often unpredictable and response strategies are frequently delayed due to resource constraints, scarcity of vaccine and logistical challenges. In Bangladesh, the risk of cholera infection is very high and studies have showed a greater than 20% risk among household contacts of cholera patients within the first 7 days after initial case presentation. As a more directed alternative to both reactive as well as routine largescale vaccination campaigns, which in Dhaka can include in excess of >1 M individuals, the “case area targeted intervention (CATI)” approach targets high-risk areas within a fixed meter radius of confirmed cholera cases, offering a rapid method for immediate cholera management with the potential for greater operational efficiency and flexibility. This study aims to evaluate the effectiveness of using CATI in densely populated cholera hotspots in and around Dhaka city. Methods/design This is a longitudinal, cluster-randomized controlled trial. The cholera index cases are identified using a rapid diagnostic test (RDT) among acute watery diarrhea patients presenting to the icddr, b Dhaka Hospital, based on inclusion and exclusion criteria. CATI is implemented by administering either a single dose or two doses of oral cholera vaccine (OCV) ‘Cholvax’, given one month apart to the index household and neighboring households within a 20–40 m radius (defined as cluster) based on the higher population density in Dhaka city, while control arms receive no intervention. Approximately 150 participants are enrolled per cluster ( N = 456 clusters), and the total study population will be ~ 68,400. Bi-annual census, active biweekly surveillance, and passive hospital-based surveillance are conducted, and study participants will be monitored over a three-year follow-up period. Discussion This study will generate critical evidence on the effectiveness of CATI using OCV dose strategies by reducing cholera incidence and has the potential to provide a rapid, efficient, and resource-sensitive alternative to mass vaccination in the cholera hotspot of Dhaka city. If effectiveness is proven through this approach, it will be used to inform policymakers to include this strategy in the national cholera control plan (NCCP) for Bangladesh to optimize outbreak response and achieve the target for cholera elimination goals. Trial registration This study is registered with ClinicalTrials.gov, number NCT07685574.